Role of acid hydrocarbon chain length on the cure kinetics and thermal degradation of epoxy- dicarboxylic acid vitrimers - Shen, Shouqi; Skordos, Alexandros A. (Elsevier, 2025)
This study investigates the cure kinetics and thermal degradation of epoxy-dicarboxylic acid vitrimers, focusing on the effect of methylene chain length. A diffusion-controlled, modified autocatalytic kinetics model was applied, based on Differential Scanning Calorimetry (DSC) data, whilst Thermogravimetric Analysis (TGA) was used to assess degradation. Increasing the methylene chain length enhanced thermal stability, with decomposition temperatures ranging from 430 °C for the hexanedioic acid formulation to 500 °C for the tetradecanedioic acid formulation. The curing process transitioned through three distinct kinetics regimes: an initial non-catalysed phase, followed by an autocatalytic stage, and finally, a diffusion-limited phase at high crosslink density. This shift leads to a 30 %-70 % reduction in apparent activation energy during the early stages. The activation energy displays a complex behaviour, initially decreasing with longer methylene sequences before rising due to competing effects of chain flexibility and reduced reactivity. Kissinger and isoconversional analyses confirmed reliable activation energy values. Despite some discrepancies in the dodecanedioic acid formulation due to secondary reactions, the model exhibits a good approximation, with an average goodness-of-fit of 84.4 %. This analysis improves understanding of vitrimer cure kinetics and thermal behaviour, providing insights for optimising industrial applications.
Keywords: Vitrimers; Epoxy resins; Dicarboxylic acids; Cure kinetics; Thermal degradation; Differential Scanning Calorimetry (DSC); Thermogravimetric Analysis (TGA); 40 Engineering; 4016 Materials Engineering; 7 Affordable and Clean Energy; Polymers; 3403 Macromolecular and materials chemistry